A review of the tribe Hyperaspidini (Coleoptera: Coccinellidae) from the Indian region - Poorani, J. (Zootaxa, 2022)
The tribe Hyperaspidini is represented by a single genus, Hyperaspis Chevrolat 1837, in the Indian subcontinent and only six species are known at present. Two species distributed in the Indian mainland, Hyperaspis leechi Miyatake 1961 and H. maindroni Sicard 1929, and one species from Nepal, H. marginaloides Canepari 1997, are reviewed and illustrated with notes on their diagnosis, biology and distribution. An updated checklist of the species known from the Indian subcontinent is provided.